An Efficient, Facial and Green Synthesis of Substituted Thiourea - Pourshamsian, Khalil; Montazeri, Naser; Shams Khameneh, Aylar (Asian Journal of Chemistry, 2011)
A series of novel substituted N,N'-di(arylaminothiocarbonyl)terephthalamide and 1,4- di(aryloylthioureido)benzene were synthesized by the reaction of terephthaloyl dichloride, ammonium thiocyanate and primary amines, 1,4-phenylenediamine and acyl halide derivatives. The reaction has been completed within 0.5 h in solvent-free condition by grinding the mixture of reactants and afforded the substituted thiourea in good yields.